CREATIVE PROBLEM SOLVING LEARNING MODEL USING QUIZIZZ APPLICATION ON STUDENTS' LEARNING OUTCOMES IN INDONESIAN LANGUAGE SUBJECTS IN GRADE VIII OF SMP NEGERI 1 CINA, BONE REGENCY - Nita Afriani; Jusman; Suhardiman (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
The use of technology in education is an alternative to improve the quality and quantity of results and processes, including sources in learning where teachers and students are required to actively use technology in the teaching and learning process. This research is a quantitative research with a quasi-experimental method . The purpose of this study was to determine the effect of the use of creative problem solving learning media based on technology using the Quizizz application on student learning outcomes in the Indonesian language subject of class VIII SMP Negeri 1 Cina, Bone Regency. The research was conducted in March-May 2024. The research location was at SMP Negeri 1 Cina, Bone Regency. Respondents were 35 students consisting of 19 male respondents and 16 female respondents. Data analysis techniques used the help of excel and spss applications. The results of the study showed that there was an effect of the use of creative problem solving learning media based on technology using the Quizizz application on student learning outcomes p value <0.05. the conclusion of this study is that there is an effect of the use of creative problem solving learning media based on technology using the Quizizz application on student learning outcomes.